2007
DOI: 10.1111/j.1365-2613.2007.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of serum clinical chemistry parameters and the identification of urinary superoxide dismutase in a carbon tetrachloride‐induced model of hepatic fibrosis in the female Hanover Wistar rat

Abstract: Carbon tetrachloride (CCl(4)) was used to induce liver fibrosis in the rat. Using this model, we have identified changes in serum and urinary clinical chemistry parameters, and characterized histopathological lesions in the liver. Two experiments were conducted. In Experiment 1, rats were dosed at six levels of CCl(4) (0.06-0.36 ml/kg) twice weekly for 6 weeks, followed by a 6-week non-dosing recovery period (week 12). Livers were removed for histology at 6 and 12 weeks and serum parameters analysed. In Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 63 publications
(90 reference statements)
3
18
0
Order By: Relevance
“…There was no evidence of CCl 4 -induced histological changes in the kidneys of any animals. This confirms findings in previous studies where it had been shown that CCl 4 only induced kidney lesions at dose levels of 1.2 ml/kg CCl 4 and above (Smyth et al 2007(Smyth et al , 2008. Accordingly, in the present study, in the absence of the histological evidence of kidney injury, it was assumed that any proteins in the urine of rats with fibrosis, and not present in the urine of control animals, were due to the induction of hepatocellular degeneration and necrosis, the resulting inflammatory response, and the development of hepatic fibrosis.…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…There was no evidence of CCl 4 -induced histological changes in the kidneys of any animals. This confirms findings in previous studies where it had been shown that CCl 4 only induced kidney lesions at dose levels of 1.2 ml/kg CCl 4 and above (Smyth et al 2007(Smyth et al , 2008. Accordingly, in the present study, in the absence of the histological evidence of kidney injury, it was assumed that any proteins in the urine of rats with fibrosis, and not present in the urine of control animals, were due to the induction of hepatocellular degeneration and necrosis, the resulting inflammatory response, and the development of hepatic fibrosis.…”
Section: Discussionsupporting
confidence: 95%
“…CCl 4 -induced oxidative stress plays a role in Kupffer cell activation and fibrogenesis (Rivera et al 2001). We have previously reported histopathological changes and markers of inflammation in CCl 4 -induced hepatic injury in the female Hanover Wistar rat (Giffen et al 2003), and more recently described CCl 4 -induced models of hepatic fibrosis and acute liver injury, also in the female Hanover Wistar rat (Smyth et al 2007(Smyth et al , 2008.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Since then many methods to establish a model of liver fibrosis have been tried [30] . Among them, hepatic fibrosis caused by CCl4 has been extensively used in experimental models in rats because hepatic responses in rats to chronic CCl4 stimulation are shown to be superficially similar to human cirrhosis [31] . Hepatocyte damage is the initial factor of hepatic fibrogenesis and activities of ALT and AST in serum are the most commonly used biochemical markers of liver injuries [32] .…”
Section: Discussionmentioning
confidence: 99%